AKHLAK TERPUJI DAN YANG TERCELA: Telaah Singkat Ihya - Hajriansyah, Hajriansyah (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2017)
Ihya 'Ulumiddin is the masterpiece of Hujjatul Islam al-Ghazali. This book, composed of four large volumes, was mentioned as a work that elaborates the understanding of Shari'ah with Sufism, and always referred too in the two contexts of thought. This paper will briefly examine the thought of al-Ghazali in this book, especially in Volume III which talks about al-Muhlikat. The approach begins with a biographical review of the author of this book, the socio-religious background in which it was written and the author's motivation, as well as the miracle of the heart, morally disgraceful and love of the world.Keyword: Al-Ghazali, Ihya ‘Ulumiddin, Volume III, Al-Muhlikat,